3D Customized Biological Tibial Intramedullary Nail Fixation for the Treatment of Fracture after Massive Allograft Bone Transplantation of Tibial Osteosarcoma: A Case Report. Issue 6 (28th April 2022) - Yang, Hongsheng; Fang, Xiang; Xiong, Yan; Duan, Hong; Zhang, Wenli
Abstract : Allograft bone fractures are critical complications in massive allograft bone transplantations. There are limited studies available on the application of 3D printing for massive allograft bone transplantation complications, and no related reports on the treatment of an allograft bone fracture with a complete biological intramedullary nail. A complex case of allograft bone fracture after massive bone transplantation for a right tibial osteosarcoma was treated with fixation of an individualized 3D printed biological tibial intramedullary nail. Prior to the operation, the intramedullary nail was designed and printed based on the results of computed tomography examination of the affected limb, and the surface of the intramedullary nail was treated with a hydroxyapatite coating. Intraoperatively, the intramedullary nail was implanted according to the preoperative 3D design plan. The intraoperative and postoperative examinations showed that the 3D printed intramedullary nail achieved good matching between the implant and the medullary cavity, and the biological coating integrated well with surrounding bone. The follow‐up results 44 months postoperatively showed that the patient was satisfied with the surgical results, where his ankle function met his daily needs, and the Musculoskeletal Tumor Society score was 24. 3D printing tibial intramedullary nail fixation can be successful in the treatment of allograft bone fractures and should be considered as a treatment of choice. In this case, the intramedullary nail matched the surrounding bone well, had good osseointegration, and the patient regained basic function. Abstract : 3D customized biological tibial intramedullary nail fixation for the treatment of massive allograft bone fracture